Dependência da anisotropia magnética efetiva em função da temperatura e concentração de níquel de amostras nanoparticuladas de NixCo1-xFe2O4 - Dalla Costa, Leonardo José (Universidade Federal de São Carlos, 2018)
The study of nanoparticles has generated great interest in recent years in several areas of research. For example, multiferroic composite magnetoelectric materials, in which ferromagnetism and ferroelectricity occur simultaneously enables, for example, the development of new sensors. In this way, the combination of ferroeletric materials and ferrites, in particular CoFe2O4 and NiFe2O4, is interesting since these materials are isolating oxides with high transition temperatures and high saturation magnetization. The effective magnetic anisotropy of the CoFe2O4 and NiFe2O4 ferrites show a significant change due to the Ni2+ and Co2+ ions distribution in their spinel structure. Besides that, the anisotropy is also associated with magnetostriction, amongst other magnetic properties of the material. Therefore, it is possible to study several magnetic properties of a material through analysis of the effect of the magnetic field and temperature on the effective anisotropy. In this work, the effective magnetic anisotropy was studied as a function of the temperature for nanocristaline nickel doped cobalt ferrite samples (NixCo1-xFe2O4 , x = 0,0; 0,25; 0,50 and 1), prepared via combustion synthesis assisted by microwaves. TEM analisys shows the nanoparticles have spherical shape with a mean grain size ranging from 50 nm to 85 nm. Magnetic characterization were performed in a Vibrating Sample Magnetic Properties Measurement system (MPMS3-VSM SQUID), by Quantum Design, with magnetization measurements in function to the temperature and the magnetic field. Effective magnetic anisotropy was obtained by adjusting the magnetization curves using the saturation of magnetization approach (LAS). The results shows the effective magnetic anisotropy of the samples NixCo1-xFe2O4 (x = 0,0; 0,25; 0,50 and 1) are in agreement with the literature, considering the values of the applied magnetic field, temperature and mean grain size. For the samples NixCo1-xFe2O4 (x = 0,25 to 0,75), the values change differently from the weighted mean between nickel and cobalt concentration, which was expected, because Co2+ ion is substituded by a Ni2+ ion in the spinel octahedral subnet, which results in a Ni-Co interaction.
Effective magnetic anisotropy dependence of temperature and nickel concentration of NixCo1-xFe2O4 nanoparticles
Keywords: Nickel ferrite; Cobalt ferrite; Effective magnetic anisotropy; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::MATERIAIS MAGNETICOS E PROPRIEDADES MAGNETICAS